A Teacher Training Manual - Dunhill, James (London : University of London Press, 1969)
The illustrated booklet, developed by the Wabanaki Ethnic Heritage Curriculum Development Project, is written for the Indian and non-Indian educator as a basic primer on the Wabanaki tribal lifestyle. The Wabanaki Confederacy is made up of the following tribes: Maliseet, Micmac, Passamaquoddy, and Penobscot. Advocating a positive approach to teaching about Native Americans in general and highlighting the Wabanaki way of life, past and present, the booklet is divided into four parts: an introduction, Native American awareness, the Wabanakis, and appendices. Within these four parts, the teacher is given a brief look at Native American education, traditional legends, the lifestyle of the Wabanaki, the Confederacy, seasonal activities, and the changes that occured when the Europeans came. An awareness of the Wabanakis in Boston and the role of the Boston Indian Council, Inc., are emphasized. Appendices include reference notes, maps, learning activities, a list of resource organizations, and an 87-item bibliography of literature and filmstrips. (Author/ERB)
Microfiche.
Keywords: Teaching; American Indian Education; Cultural Awareness; Elementary Secondary Education; Enrichment Activities; Legends; Life Style; Resource Materials; Teacher Qualifications; Tribes; Urban American Indians; Teacher Awareness -- Wabanaki Confederacy; American Indian History -- Boston Indian Council MA -- Maliseet (Tribe) -- Micmac (Tribe) -- Passamaquoddy (Tribe) -- Penobscot (Tribe) -- Seasons; Guides, Non-Classroom.